Characteristics of deformation and defect of shield tunnel in coastal structured soil in China - Fanyan Meng; Bo Hu; Renpeng Chen; Hongzhan Cheng; Huaina Wu (Underground Space)
Shield tunnel is a type of linear underground structure assembled by lining segments, characterized with long joint, weak stiffness, and strict deformation control requirement. The situation of the long-term deformation and defect of the shield tunnel in soft ground in coastal area of China is severe, mainly attributed to the tunneling-induced ground consolidation, frozen cross passage, groundwater pumping, cyclic train load, and nearby construction. Shield tunnel is buried in ground, and the above factors could result in underlying ground settlement, overlying ground loading/unloading, and at-side ground unloading. As a result, the tunnel could suffer from different types of structural deformation and defect. Based upon the aforementioned different reasons, this study investigates the characteristics of the tunnel deformation and defect corresponding to the different types of ground stress change and deformation. It is found that tunneling-induced ground consolidation, frozen cross passage, groundwater pumping, and cyclic train load mainly contribute to the longitudinal differential settlement but negligible transverse convergence, associated with water leakages at circumferential joints. In comparison, surface surcharge and at-side unloading not only cause significant longitudinal differential deformation but also increase transverse lining internal forces, resulting in water leakages at circumferential joints, longitudinal lining concrete cracks and water leakages. Finally, nearby construction could strongly disturb the ground and cause the generation of excess pore-water pressure, making the shield tunnel deformation develops continuously after the nearby construction is completed.